Study of special aspects of hitching to wide span tractors (vehicles) - Bulgakov, V.; Arak, M.; Olt, J.; Holovach, I.; Kuvachov, Volodymyr; Кувачов, Володимир Петрович; Кувачев, Владимир Петрович (My University, 2018)
The paper presents the research into the specific aspects of hitching agricultural machines and implements to wide span tractors (vehicles). According to the results of the performed investigations, the redistribution of the normal reaction forces on the tractor’s front and rear wheels depends to a significant extent not only on the inclination of the hitch links of the wide span tractor (vehicle), but also on such design parameters as the distance from the linkage to the centre of resistance and the carrier wheel of the agricultural machine or implement. In order to exclude in practical terms completely the effect of the machines’ running gear compacting the soil in the yielding (agronomic) zones of the field, it is recommended to implement on the wide span tractors (vehicles) the controlling devices that allow adjusting the normal vertical load on the agricultural machine or implement’s carrying wheels. Such controlling devices can operate on the principle of the known weight transfer traction boosters used in conventional tractors.
Исследование особенностей агрегатирования мостовых тракторов
Keywords: tractors